The effect of multiple scattering on optical measurement of soot emissions in atmospheric plumes. (October 2020) - Conrad, B.M.; Thornock, J.N.; Johnson, M.R.
Highlights: Optical measurements of soot are complicated by multiple scattering (MS) effects. Complex MS in turbulent soot-laden plumes can be captured by a simple MS model. MS model permits use of single-scattering assumption in radiative transfer analyses. Sky-LOSA case studies show value of MS model in correcting bias due to MS. Abstract: Measurements of soot/black carbon emissions via optical observations of atmospheric plume transmittance require a correction to account for bias in perceived plume brightness due to inscatter of ambient light. The ability to accurately correct for inscattering is hampered, however, by the potential for multiple scattering (MS) within the plume, which cannot be directly considered without detailed knowledge of the turbulent plume's structure. MS is thus oft-ignored within such measurement techniques, resulting in an inherent upward bias in calculated emissions. In this work, Monte Carlo "ray tracing" (MCRT) analyses for realistic lines-of-sight through large-eddy simulated, soot-laden atmospheric plumes of gas flares were used as case study data for analysis of MS effects. Through a reverse MCRT procedure, a remarkably simple yet accurate model was derived that relates the quantity of inscattered light under MS conditions to an estimate assuming single-scattering. Case study data from previous field measurements of gas flares using the sky-LOSA technique demonstrate that neglecting MS effects can bias reported soot emission rates by up to and exceeding one-quarter of typical measurement uncertainties. Coupling this model with an additional procedure to correct for minor model biases allows the complex influence of multiple scattering to be directly and accurately considered in optical measurements of soot emissions.